A Study on Factors Influencing Consumer Behaviour to Use Foodpanda in Malaysia - Muhammad Adam; Mohamad Mu’Ammar; Mohd Nooramirul Najmi; Muhammad Alief; Adityanarayan Janardan Gop; Pranav Anant Joshi (AIBPM Publisher, 2023)
As we embark on the twenty-first century, technology has changed our lives. All the daily activities and transactions can be done at our fingertips. Foodpanda is the best food delivery platform for FB merchants in Malaysia. Consumers can place their food orders from any kind of restaurant in Malaysia and consumers nowadays preferred to order online as it is convenient, flexible and less move required. This study aims to examine the factors influencing consumer behaviour to use Foodpanda in Malaysia. The key factors that we examine is perceived ease of use, perceived price, perceived trust and perceived service quality that impacted customer behaviour. A total of 150 Foodpanda users participated in the online survey via Google Forms. The findings of this study provide new insights to customers on how consumer behaviour is being related to the usage of Foodpanda delivery platform.Â Keywords: Foodpanda, perceived ease of use, perceived price, perceived trust, perceived service quality, customer behaviour.